2019
DOI: 10.1109/jstqe.2019.2914423
|View full text |Cite
|
Sign up to set email alerts
|

A 6 × 30 Gb/s Tunable Transmitter PIC With Low RF Crosstalk From an Open-Access InP Foundry

Abstract: DOI to the publisher's website.• The final author version and the galley proof are versions of the publication after peer review.• The final published version features the final layout of the paper including the volume, issue and page numbers. Link to publication General rightsCopyright and moral rights for the publications made accessible in the public portal are retained by the authors and/or other copyright owners and it is a condition of accessing publications that users recognise and abide by the legal re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…Each generated beam passes through a semiconductor optical amplifier (SOA) and an external electro-absorption modulator at 10 Gbit/s in baseband operation [225]. Yao et al [226] demonstrated a six-channel array based on EML using Mach-Zehnder modulators integrated into a InP platform. The baseband non-return to zero (NRZ) optical signals were transmitted at 20 Gbit/s and 30 Gbit/s throughputs.…”
Section: E Imwp-integrated Microwave Photonicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Each generated beam passes through a semiconductor optical amplifier (SOA) and an external electro-absorption modulator at 10 Gbit/s in baseband operation [225]. Yao et al [226] demonstrated a six-channel array based on EML using Mach-Zehnder modulators integrated into a InP platform. The baseband non-return to zero (NRZ) optical signals were transmitted at 20 Gbit/s and 30 Gbit/s throughputs.…”
Section: E Imwp-integrated Microwave Photonicsmentioning
confidence: 99%
“…The baseband non-return to zero (NRZ) optical signals were transmitted at 20 Gbit/s and 30 Gbit/s throughputs. The photodetected signals were analyzed using the eye diagram and BER [226].…”
Section: E Imwp-integrated Microwave Photonicsmentioning
confidence: 99%
“…P HOTONIC integrated circuits (PICs), extensively explored in research, hold the potential for applications across diverse fields, such as high-speed transceivers in optical communications [1], integrated photonic switches in data centers and high-performance computing systems [2], and dense optical phased arrays for precise sensing and ranging [3]. Temperature plays a critical role in the performance and reliability of PICs [4], particularly within high-performance PICs that contain optical amplifiers, arrayed waveguide gratings, or lasers.…”
Section: Introductionmentioning
confidence: 99%